Use of antibiotics in COVID-19 ICU patients - Lirim Mustafa; Ilir Tolaj; Nehat Baftiu; Hajrullah Fejza (Journal of Infection in Developing Countries)
Introduction: The role of antibiotics in the treatment in COVID-19 cases has not yet been adequately defined, and no criteria have been established for antibiotic treatment, type and duration.